Factores de dinámica social asociados al índice de masa corporal en adultos en México - Rodríguez Oreggia, Eduardo; Pérez Lizaur, Ana Bertha (El Colegio de México, A.C., 2010)
This paper aims to relate factors from social dynamics, form the household and same cohort, with the body mass index (BMI) of adults in Mexico. Using panel data from the National Survey for Households Living (ENNVIH), 2002 and 2005, we model associated factors to BMI, controlling for nutritional, use of time, and illnesses variables. Results show significative effects from the interaction between obesity and overweight in the household and with same groups of age, being consistent with the use of random and fixed effects by individual and households.